2016
DOI: 10.1016/j.amjmed.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring for Pulmonary Hypertension Following Pulmonary Embolism: The INFORM Study

Abstract: Despite exhibiting pulmonary hypertension-related symptoms, many pulmonary embolism patients did not undergo imaging tests that could diagnose pulmonary hypertension or chronic thromboembolic pulmonary hypertension. This study suggests that physician education about the risk of pulmonary hypertension and chronic thromboembolic pulmonary hypertension after pulmonary embolism may need to be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 29 publications
1
38
0
3
Order By: Relevance
“…While the weighted average incidence of CTEPH after an acute PE of 4% in this study was generally similar to the weighted incidence of 3.8% determined in the INFORM study [57], a subsequent and recent systematic review and meta-analysis of 16 studies has suggested lower incidences of CTEPH after acute PE: 0.56% in "all comers" (n=1186), 3.22% in "survivors" (n=999) and 2.79% in "survivors without major comorbidities" (n=1775) [72], which suggests that the full incidence of CTEPH may be lower. As PEA is performed infrequently in Japan, with physicians favouring BPA, the diagnosis rate for Japan is an assumption, based on the diagnosis rates calculated for the other countries; however, there is a possibility that the real figure is higher.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…While the weighted average incidence of CTEPH after an acute PE of 4% in this study was generally similar to the weighted incidence of 3.8% determined in the INFORM study [57], a subsequent and recent systematic review and meta-analysis of 16 studies has suggested lower incidences of CTEPH after acute PE: 0.56% in "all comers" (n=1186), 3.22% in "survivors" (n=999) and 2.79% in "survivors without major comorbidities" (n=1775) [72], which suggests that the full incidence of CTEPH may be lower. As PEA is performed infrequently in Japan, with physicians favouring BPA, the diagnosis rate for Japan is an assumption, based on the diagnosis rates calculated for the other countries; however, there is a possibility that the real figure is higher.…”
Section: Discussionsupporting
confidence: 61%
“…The full incidence was calculated based on a weighted average of 4% for the proportion of patients who develop CTEPH after PE. Data from the INFORM study, a retrospective US-based claims analysis, suggested the proportion of PE patients developing CTEPH to be 3.8% [57], which is close to the weighted average used in this analysis. A recent review by KIM [58] estimates full incidence of CTEPH in the USA to be 4886 cases per year, based on an incidence of CTEPH after PE of 0.57%, as reported by KLOK et al [50], while the diagnosed incidence of CTEPH in Spain, the UK and Germany is reported to be 0.9, 1.75 and 4 cases per million, respectively [59].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, systematic description of results of serial imaging by CTPA and Q lung scanning in the long term after acute PE and relation to functional outcome is largely lacking. For example, in a retrospective database analysis, Tapson et al6 showed that only 20% of patients had repeat CTPA and 6% had repeat ventilation/perfusion following acute PE. Furthermore, to our knowledge, the correlation between findings or change in findings over time on imaging and long‐term functional exercise limitation after PE has yet to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…18 A claim database analysis suggests that less than 50% of patients with PE are evaluated with a follow-up echocardiogram. 19 Whether or not this is sufficient remains to be determined.…”
Section: Epidemiologymentioning
confidence: 99%